Seismic velocity structure and its implications for oceanic mantle hydration in the trench–outer rise of the Japan Trench. Issue 3 (21st February 2019) - Obana, Koichiro; Fujie, Gou; Takahashi, Tsutomu; Yamamoto, Yojiro; Tonegawa, Takashi; Miura, Seiichi; Kodaira, Shuichi
SUMMARY: Oceanic plates play an important role in transporting water from Earth's surface into the mantle. The trench–outer rise region is one of the places where hydration of the oceanic plate occurs. We investigated oceanic plate hydration in the trench–outer rise region of the Japan Trench on the basis of the seismic velocity structure as estimated by a tomographic analysis of data from ocean bottom seismograph arrays. This analysis demonstrates a reduction in P- wave and S- wave velocity ( Vp and Vs ) within the uppermost oceanic mantle of the incoming Pacific plate in the direction towards the trench axis. This seismic velocity reduction, which was observed in at least the uppermost 15 km of the mantle, is consistent with hydration of the uppermost mantle due to infiltration of water through the oceanic crust along bending-related normal faults. Under the assumption that the velocity reduction is caused solely by serpentinization of the mantle, the Vp changes suggest that water content increases by about 1.1 to 2.9 wt per cent at depths as great as 15 km below the oceanic Moho. An increase in water-filled fractures can also account for this velocity reduction with a smaller amount of water. Aside from the general trend of velocity reduction towards the trench axis, the Vp structure of the incoming plate shows spatial heterogeneity related to mantle seismicity, in that earthquakes within the uppermost mantle generally coincide with areas of low Vp . This spatial seismic heterogeneity is consistent with localized hydration or formation of water-filled fractures along bending-related normal faults. Hence, a low- Vp anomaly within the uppermost oceanic mantle could be an indicator of possible sites of large outer-rise normal-faulting earthquakes in which the rupture extends into the mantle.